Analytic network process and balanced scorecard applied to the performance evaluation of public health systems - Dos Santos, Marco Aurélio Reis [UNESP]; Salomon, Valério Antonio Pamplona [UNESP]; Marins, Fernando Augusto Silva [UNESP] (FapUNIFESP (SciELO), 2015)
The performance of public health systems is an issue of great concern. After all, to assure people’s quality of life, public health systems need different kinds of resources. Balanced Scorecard provides a multi-dimensional evaluation framework. This paper presents the application of the Analytic Network Process and Balanced Scorecard in the performance evaluation of a public health system in a typical medium-sized Southeastern town in Brazil.
Keywords: Analytic network process; Balanced scorecard; Performance evaluation; Public health systems